ANALYSIS OF INTERNET CONNECTION SPEED AND QUALITY IN 4G AND 5G NETWORK TECHNOLOGY - Syahfitri, Najwa Khairani; Arhan Syaputra Siregar; Abiyyu adzin; Adelyna Oktavia Nasution (Bahasa Indonesia, 2025)
This study aims to compare the quality of 4G and 5G networks, focusing on download/upload speeds and key parameters such as RSRP, RSRQ, throughput, latency, and packet loss. Based on literature review, 5G outperforms 4G significantly in speed and efficiency. Telkomsel’s 5G throughput is 1453.25 kbps and XL’s is 1319 kbps (both “good” by TIPHON). Packet loss rates are low: 1.65% (Telkomsel) and 1.575% (XL), “excellent” by standard. In contrast, 4G networks show variable quality and higher instability. This highlights the need for infrastructure enhancement in 5G expansion.